2017
DOI: 10.1186/s13018-017-0619-7
|View full text |Cite
|
Sign up to set email alerts
|

High-grade bursal-side partial rotator cuff tears: comparison of mid- and long-term results following arthroscopic repair after conversion to a full-thickness tear

Abstract: BackgroundPartial-thickness rotator cuff tears (PTRCTs) are one of the leading causes of shoulder dysfunction. Successful results have been reported with different treatment techniques, but the long-term consequences of these procedures are not yet clearly known. The purposes of this study were to evaluate and compare the mid- and long-term clinical outcomes of arthroscopically repaired bursal-side PTRCTs after conversion to full-thickness tears and identify the possible effects of age, gender, and hand domina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Included in the meta-analysis of postoperative Constant-Murley scores were 7 studies 1 , 6 , 9 , 10 , 13 , 20 , 21 with a total of 482 male and 354 female patients. The mean postoperative Constant-Murley score was 76.77 ± 15.94 for male patients and 69.88 ± 17.02 for female patients.…”
Section: Resultsmentioning
confidence: 99%
“…Included in the meta-analysis of postoperative Constant-Murley scores were 7 studies 1 , 6 , 9 , 10 , 13 , 20 , 21 with a total of 482 male and 354 female patients. The mean postoperative Constant-Murley score was 76.77 ± 15.94 for male patients and 69.88 ± 17.02 for female patients.…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with our finding for ASES, a quicker return to work and greater improvement in patient-reported disability with surgery on the dominant side has previously been reported. 1,32 Regarding the delayed achievement trend we found in Constant score, Aydin and Karaismailoglu 3 showed that surgery on the dominant side led to less improvement in Constant scores compared with nondominant-side surgery. Despite the seeming disparity of these findings, they could be reporting a similar trend, albeit measured by different metrics.…”
Section: Discussionmentioning
confidence: 81%
“…The full-thickness suture method exposes the bone bed by debridement of the damaged tendon stump, and suturing is performed in a standard manner. This method is convenient and easily mastered by most surgeons [ 20 ]. In addition, animal experiments have shown that full-thickness suturing has better outcomes than in situ repair, which may be related to the more thorough debridement that is done in full-thickness suturing [ 21 ].…”
Section: Discussionmentioning
confidence: 99%